Internalization of the Prophet’s Eating Etiquette through the Free Nutritious Meals Program in Shaping Students’ Religious Character - Khoeru Romadon; Dede Siska Amaliyah; Talina (BAYAN: Jurnal Studi Islam dan Humaniora, 2026)
This study aims to describe the internalization of the Prophet Muhammad’s eating etiquette through the Free Nutritious Meals Program in forming the religious character of eleventh-grade students at MA Ulul Absharr. This study used a descriptive qualitative method with a case study design. Data were collected through observation, interviews, and documentation involving the madrasah principal, Islamic education teachers, homeroom teacher, students, and parties involved in the meal program. The findings show that the Free Nutritious Meals Program was not only implemented as a food distribution activity, but also functioned as a pedagogical space for habituating religious values. Teachers guided students to recite basmalah, eat with the right hand, maintain order, avoid criticizing food, eat moderately, keep the eating area clean, and recite hamdalah after eating. These practices supported the formation of gratitude, discipline, responsibility, simplicity, cleanliness, politeness, and social care. The study concludes that the meal program can strengthen religious character when it is integrated with teacher role modeling, habituation, supervision, and Islamic value reinforcement.